Assessing medical impoverishment and associated factors in health care in Ethiopia - Amarech G. Obse; John E. Ataguba (BMC, 2020)
Abstract Background About 5% of the global population, predominantly in low- and middle-income countries, is forced into poverty because of out-of-pocket (OOP) health spending. In most countries in sub-Saharan Africa, the share of OOP health spending in current health expenditure exceeds 35%, increasing the likelihood of impoverishment. In Ethiopia, OOP payments remained high at 37% of current health expenditure in 2016. This study assesses the impoverishment resulting from OOP health spending in Ethiopia and the associated factors. Methods This paper uses data from the Ethiopian Household Consumption Expenditure Survey (HCES) 2010/11. The HCES covered 10,368 rural and 17,664 urban households. OOP health spending includes spending on various outpatient and inpatient services. Impoverishing impact of OOP health spending was estimated by comparing poverty estimates before and after OOP health spending. A probit model was used to assess factors that are associated with impoverishment. Results Using the Ethiopian national poverty line of Birr 3781 per person per year (equivalent to US$2.10 per day), OOP health spending pushed about 1.19% of the population (i.e. over 957,169 individuals) into poverty. At the regional level, impoverishment ranged between 2.35% in Harari and 0.35% in Addis Ababa. Living in rural areas (highland, moderate, or lowland) increased the likelihood of impoverishment compared to residing in an urban area. Households headed by males and adults with formal education are less likely to be impoverished by OOP health spending, compared to their counterparts. Conclusion In Ethiopia, OOP health spending impoverishes a significant number of the population. Although the country had piloted and initiated many reforms, e.g. the fee waiver system and community-based health insurance, a significant proportion of the population still lacks financial protection. The estimates of impoverishment from out-of-pocket payments reported in this paper do not consider individuals that are already poor before paying out-of-pocket for health services. It is important to note that this population may either face deepening poverty or forgo healthcare services if a need arises. More is therefore required to provide financial protection to achieve universal health coverage in Ethiopia, where the informal sector is relatively large.